Las habilidades blandas y su influencia en el desempeño laboral del personal de los subcentros de salud de Calceta - Sanclemente Zambrano, Ana Lina (2023)
The softs skills have gained a significant boom in recent decades, since these are required in organizations more frequently, for this reason, this research has the purpose of analyzing the soft skills of the officials of the health sub-centers in Calceta, and its influence on job performance to improve the quality of service, using a methodology according to the needs, where through scientific methods such as inductive, deductive and analytical-synthetic, there was a generation of knowledge related to the subject of study, also, various instruments were implemented to collect information and data, such as the interview and survey, which showed various results, where the most significant were: the deficiency of time management skills, lack of staff motivation and low levels of leadership, since the lack of these skills causes limitations in the development of the activities of health center employees, resulting in poor quality service delivery. However, based on these limitations, an improvement plan was generated to strengthen these attitudes in the employees. In summary, soft skills are fundamental in the health sub-centers, since they foster an empathetic and communicative culture in the work performance of the employees, contributing to the delivery of a more humane, efficient and quality service